Español (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
Violence against indigenous women and girls is intertwined with multiple forms of discrimination and structural inequality. Violations of the collective rights of indigenous peoples and nations constitute a form of inequality that differentially affects and impacts men, women, and non-binary gender identities especially in extractivist contexts. Understanding the right to health from an intersectional and intercultural perspective is still a pending task in the public policy arena in Argentina; This is a vitally relevant task if we seek to consolidate a democratic, egalitarian, just, and violence-free society. This article starts by understanding gender-based violence as a public health issue that requires an attentive approach to the specific demands and lived experiences of native women, as subjects of rights. A theoretical reflection work is proposed in dialogue with data constructed from in situ observation.